Public debt places no burden on future generations under demand shortage - Takayuki Ogawa; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2010)
In a Diamond-type overlapping-generations setting public debt issuance places no burden on future generations including those who repay the debt if prices and wages are fixed and unemployment occurs in the periods in which public bonds are issued and repaid. Whether the collected fund is spent on government purchases or transfers to the present generation, public bond issuance stimulates aggregate demand and creates additional employment of future generations, which yields additional income that is large enough to cover their tax burden. This property is true whether the debt is repaid by children or grandchildren.
Keywords: E24; E62; H63; 330; demand shortage; overlapping generations; public debt; unemployment; welfare effects; Gesamtwirtschaftliche Nachfrage; Öffentliche Schulden; Arbeitslosigkeit; Wohlfahrtsanalyse; Overlapping Generations; Theorie